Radioiodine Induced Salivary and Lacrimal Gland Dysfunction in Differentiated Thyroid Carcinoma Patients: An Observational Study (Bangladesh Journal of Nuclear Medicine, 2025)
Background: This study was carried out to assess the radioiodine (I131) induced salivary and lacrimal gland damage in differentiated thyroid carcinoma (DTC) patients. Material and Methods: A total 124 patients with differentiated thyroid carcinoma (DTC) were included in this observational study. These patients underwent radioiodine (I131) ablation following total thyroidectomy at INMAS, Mitford and completed a minimum follow-up period of 60 months. Symptoms indicative of salivary and lacrimal gland damage (xerostomia, dysphagia, salivary gland pain, swelling, dysgeusia, dry eye, excess lacrimation) were evaluated during follow up using standard questionnaires. Morphological changes of major salivary glands were assessed using high resolution ultrasound. Result: A total of 46 (37.10%) patients experienced salivary gland symptoms where xerostomia (34, 27.4%) was the most common. Lacrimal gland symptoms found in 12 (9.60%) patients. Ultrasound features of chronic sialadenitis were observed in 10 (7.80%) patients. Conclusion: Salivary gland damage is a common manifestation of thyroid cancer patient after radioiodine ablation.Bangladesh J. Nuclear Med. 27(2): 197-201, 2024